Contagion : Monsoonal Effects, Spillovers, and Jumps Between Multiple Equilibria - Masson, Paul. (Washington, D.C. : International Monetary Fund, 1998)
Several concepts of contagion are distinguished. It is argued that only models that admit of multiple equilibria are capable of producing true contagion. A simple balance of payments model is presented to illustrate that phenomenon, and some back-of-the-envelope calculations assess its relevance to the coincidence of emerging market crises in 1994-95 and in 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet